2019
DOI: 10.5194/acp-19-2441-2019
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of black carbon (BC) aerosol impact over Hindu Kush Himalayan sites: validation, sources, and implications on glacier runoff

Abstract: Abstract. We estimated the black carbon (BC) concentration over the Hindu Kush Himalayan region (HKH), its impact on snow albedo reduction, and sensitivity on annual glacier runoff over the identified glaciers. These estimates were based on free-running aerosol simulations (freesimu) and constrained aerosol simulations (constrsimu) from an atmospheric general circulation model, combined with numerical simulations of a glacial mass balance model. BC concentration estimated from freesimu performed better over hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 66 publications
3
22
0
Order By: Relevance
“…However, it is also noted from the evaluation of BC concentration estimated from the free-running aerosol simulations using Laboratoire de Météorologie Dynamique atmospheric general circulation model (LMDZT-GCM) that simulated BC which is underestimated by a significant factor at stations which are close to emission sources (such as that over mainland India), exhibit a relatively lower discrepancy with observed BC concentration over the Indian oceanic regions (Reddy et al, 2004;Verma et al, 2007Verma et al, , 2011. The simulated BC distribution from LMDZT-GCM was also found to match consistently well the available observations at high altitude Himalayan Hindukush stations (e.g., Hanle, Satopanth)) which are relatively remotely located and mostly influenced by the transport of aerosols (Santra et al, 2019). The above evaluations, therefore, suggest that the large underestimation of BC concentration over the India mainland would primarily be due to BC emission dataset, instead of the model configurations.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…However, it is also noted from the evaluation of BC concentration estimated from the free-running aerosol simulations using Laboratoire de Météorologie Dynamique atmospheric general circulation model (LMDZT-GCM) that simulated BC which is underestimated by a significant factor at stations which are close to emission sources (such as that over mainland India), exhibit a relatively lower discrepancy with observed BC concentration over the Indian oceanic regions (Reddy et al, 2004;Verma et al, 2007Verma et al, , 2011. The simulated BC distribution from LMDZT-GCM was also found to match consistently well the available observations at high altitude Himalayan Hindukush stations (e.g., Hanle, Satopanth)) which are relatively remotely located and mostly influenced by the transport of aerosols (Santra et al, 2019). The above evaluations, therefore, suggest that the large underestimation of BC concentration over the India mainland would primarily be due to BC emission dataset, instead of the model configurations.…”
Section: Introductionsupporting
confidence: 64%
“…Possible reasons suggested for the discrepancy between model and observations included, lack of BC emissions used as input, inadequate meteorology, and representation of aerosol treatment, and coarse resolution in the model (e.g. Santra et al, 2019;Kumar et al, 2018;Wang et al, 2016;Pan et al, 2015;Verma et al, 2011;Reddy et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, LAPs can directly interact with incoming solar radiation and induce thermodynamical modifications to synoptic-scale circulations (Hansen et al, 1997;Ramanathan et al, 2001;Bond et al, 2013;Lau et al, 2006;Bollasina et al, 2011;Li et al, 2016). Secondly, acting as cloud condensation nuclei, changes in concentrations of these particles can lead to microphysical modification of cloud systems and precipitations Li et al, 2016;Qian et al, 2009;Sarangi et al, 2017). Finally, deposition of LAPs in the snowpack can also darken the snow, reduce its surface albedo, and accelerate snow warming and melting (Warren and Wiscombe, 1980;Qian et al, 2015Qian et al, , 2011Qian et al, , 2009Lau et al, 2010;B.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, indicating that the inadequate BC distribution would lead to the dilution of the population exposure and the reduction of population-weighted concentration. A better agreement between model simulated and observed magnitude of atmospheric aerosol species was, however, delivered over the Indian region in a recent study using the constrained aerosol simulation approach 7,16 . Further, the constrained BC emissions were estimated over the Indian region constraining the simulated BC concentration in a general circulation model (Laboratoire de Météorologie Dynamique atmospheric General Circulation Model (LMDZT-GCM)) with the observed BC (observationally-constrained BC emissions) by combining forward and receptor modelling approaches 12 .…”
Section: Methodsmentioning
confidence: 96%
“…Available studies indicated that the most likely reasons for the discrepancy between model and observations include an underestimation of BC emissions used as input, inadequate meteorology and representation of aerosol treatment, and too coarse spatial resolution in the model 7,11,[16][17][18][19] . In a recent study 20 , an improvement in model performance relative to observations over the East and South Asia regions was shown with a high-resolution chemical transport model, revealing an overlap of high BC exposure concentration and population density.…”
Section: Methodsmentioning
confidence: 99%